Evaluation of the Food Estate Program for Achieving Food Security: Evaluasi Program Food Estate untuk Mencapai Keamanan Pangan - Martani, Rifqi Fakhrian; Bainus, Arry; Rahmatunnisa, Mudiyati (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Indonesia continues to face recurring instability in food availability, marked by fluctuating prices and frequent shortages of staple commodities. Specific background: The Food Estate Program, introduced in 2020, was launched as a large-scale agricultural strategy intended to strengthen national food reserves and reduce vulnerability to supply disruptions. Knowledge gap: Despite extensive discussion, there remains limited integrated analysis comparing policy expectations with actual implementation outcomes across different regions. Aims: This study evaluates the program’s performance in relation to its stated goal of achieving national food security. Results: The evaluation shows that major constraints persist, including land unsuitability for selected crops, environmental degradation, recurrent crop failures, low productivity, inadequate scientific assessments, corporate-centered decision-making, and limited participation of local farmers. Novelty: This research provides a consolidated, multi-site evidence review that highlights disparities between program design and field conditions. Implications: Findings indicate the need for more context-based land evaluation, transparent governance mechanisms, strengthened farmer involvement, and collaboration with independent research institutions to support more coherent pathways toward national food security. Highlights • Program implementation shows clear gaps between planned design and field realities.• Limited farmer involvement contributes to mismatched crop selection and low yields.• Evidence from multiple regions indicates recurring technical and governance challenges. Keywords Food Estate Program, Food Security, Policy Evaluation, Agricultural Governance, Farmer Participation